Becoming Socialized into a New Professional Role: LPN to BN Student Nurses' Experiences with Legitimation - Sherri Melrose; Jean Miller; Kathryn Gordon; Katherine J. Janzen (Nursing Research and Practice)
This paper presents findings from a qualitative descriptive study that explored the professional socialization experiences of Licensed Practical Nurses (LPNs) who attended an online university to earn a Baccalaureate degree in nursing (BN), a prerequisite to writing the Canadian Registered Nurse (RN) qualifying exam. The project was framed from a constructivist worldview and Haas and Shaffir’s theory of legitimation. Participants were 27 nurses in a Post-LPN to BN program who came from across Canada to complete required practicums. Data was collected from digital recordings of four focus groups held in different cities. Transcripts were analyzed for themes and confirmed with participants through member checking. Two overarching themes were identified and are presented to explain how these unique adult learners sought to legitimize their emerging identity as Registered Nurses (RNs). First, Post-LPN to BN students need little, if any, further legitimation to affirm their identities as “nurse.” Second, practicum interactions with instructors and new clinical experiences are key socializing agents.